Reconsidering the “gang effect” in the face of intermittency: do first- and second-time gang membership both matter? - Augustyn, Megan Bears (Criminology, 2021)
Support for the Rochester Youth Development Study has been provided by the National Institute on Drug Abuse (R01DA05512), the Office of Juvenile Justice and Delinquency Prevention (86-JN-CX-0007, 96-MU-FX-0014, 2004-MU-FX-0062), the National Science Foundation (SBR-9123299), and the National Institute of Mental Health (R01MH63386). Technical assistance for this project also was provided by an NICHD grant (R24HD044943) to the Center for Social and Demographic Analysis at the University at Albany. Points of view or opinions expressed in the article are those of the authors and do not necessarily represent the official position or policies of the funding agencies. The authors also would like to thank Carter Hay and four anonymous reviewers at CRIMINOLOGY for their insightful feedback and comments and Robert Brame and Laura Dugan for their feedback on analytic strategies.